Pengembangan Sistem Repository Dokumen Teknis Berbasis Web di PT Semen Padang pada Unit Site Engineering - Muriyanto, Annur Wahid; Adri, Muhammad; Irfan, Dedy; Darni, Resmi (TSAQOFAH, 2025)
The advancement of information and communication technology has driven significant transformation in document management across various institutions, including corporations. This study aims to develop a web-based technical document repository system for the Site Engineering Unit at PT Semen Padang to address the limitations of manual management and improve efficiency in document retrieval and security. The method employed is software development using the Agile approach, encompassing planning, system design with Unified Modeling Language (UML), system development using the Vue.js and Laravel frameworks, testing through the BlackBox method, and implementation of User Acceptance Testing (UAT). The results indicate that the system successfully modeled actor interactions through UML and passed functional testing. All core features, such as login, document management, role settings, audit trail, and document search—operated effectively without errors. The study concludes that the implementation of a web-based technical document repository system significantly enhances operational efficiency, accelerates retrieval processes, and strengthens document management security within the Site Engineering Unit at PT Semen Padang. The research also recommends further exploration of artificial intelligence integration to optimize system functionality in the future.